2017
DOI: 10.1016/j.stemcr.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Characterization of Mesenchymal Stem/Stromal Cells from a Large Cohort of AML Patients Demonstrates a Definitive Link to Treatment Outcomes

Abstract: SummaryBone marrow mesenchymal stem/stromal cells (BM-MSCs) are key components of the hematopoietic niche thought to have a direct role in leukemia pathogenesis. BM-MSCs from patients with acute myeloid leukemia (AML) have been poorly characterized due to disease heterogeneity. We report a functional, genetic, and immunological characterization of BM-MSC cultures from 46 AML patients, stratified by molecular/cytogenetics into low-risk (LR), intermediate-risk (IR), and high-risk (HR) subgroups. Stable MSC cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 58 publications
4
83
0
Order By: Relevance
“…5 Lenalidomide and pomalidomide possess pleiotropic anti-tumor properties including also tumor-controlling immune-modulating effects in other hematological BM malignances such as MDS and MM. 9-11 We therefore set out to assess the anti-leukemia effects of lenalidomide and pomalidomide in AML.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…5 Lenalidomide and pomalidomide possess pleiotropic anti-tumor properties including also tumor-controlling immune-modulating effects in other hematological BM malignances such as MDS and MM. 9-11 We therefore set out to assess the anti-leukemia effects of lenalidomide and pomalidomide in AML.…”
Section: Resultsmentioning
confidence: 99%
“…In AML, the high rate of relapse may in part be a result of the inability of current treatments to effectively overcome the protective influence of the BM niche. 5,46 In fact, it has been recently shown that BM mesenchymal stromal cells (BM-MSCs) derived from diagnostic AML patients are strong immunomodulators and provide similar or even higher chemoprotection of AML cells to cytarabine/idarubicin than normal BM-MSCs. 5 Therefore, new compounds or improved combinatory regimens targeting the interaction between the BM microenvironment and AML leukemic cells are very attractive candidates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations